Efektivitas Strategi Promosi Produk Kopi Lokal di Rumah Kopi Ranin - Muhammad Arismal Rezki; Dwi Retno Hapsari (Jurnal Komunikasi Pembangunan, 2019)
Ranin Coffee House is a small scale business that is engaged in selling local coffee products. This business conducts promotional activities to increase sales of its products. The purpose of this study is to identify the form of promotional strategies, analyze the effectiveness of promotional strategies, and identify the relationship between respondent characteristics and the effectiveness of promotional strategies on the dimensions of empathy, persuasion, impact, and communication. This research was used a quantitative approach in a survey of 40 respondents who were supported by qualitative data with in-depth interviews with selected respondents who mastered the research problem. The results show that brand and packaging promotion strategies, Instagram media, and personal selling are counted effective in increasing empathy, persuasion, positive impact, and communication (EPIC dimension), and not all respondent characteristics are related to the effectiveness of promotional strategies carried out by Ranin Coffee House.